Empowering Women and Building Sustainable Food Systems: A Case Study of Cuba's Local Agricultural Innovation Project - Benítez, Barbara; Nelson, Erin; Romero Sarduy, María Isabel; Ortíz Pérez, Rodobaldo; Crespo Morales, Anaisa; Casanova Rodríguez, Caridad; Campos Gómez, Maybe; Méndez Bordón, Aliek; Martínez Massip, Annia; Hernández Beltrán, Yaima; Daniels, Jordan (Frontiers in Sustainable Food Systems, 2020)
This paper presents a case study of Cuba's Local Agricultural Innovation Project (PIAL for its initials in Spanish), with a focus on its gender-specific elements. The PIAL methodology was first introduced in Cuba in the early 2000's as a means of carrying out participatory plant-breeding to facilitate the development and use of locally-adapted seed varieties and help farmers diversify their production. A cornerstone of Cuba's transition toward more agroecological production, PIAL currently operates in 75 municipalities across 12 provinces and in the Isle of Youth special municipality, and the model has evolved from its initial focus on participatory plant-breeding to include more holistic programming aimed at increasing food system sustainability and community resilience. In this paper we highlight how the gender-specific aspects of the PIAL model facilitate female participation and leadership and how this contributes to positive economic, ecological and sociocultural changes in farming households and communities. Key impacts include: increased inclusion of women in developing and implementing farm innovations; increased self-confidence for female farmers and farm-family members; increased productive diversification on family farms; and, increased employment and household income through women-led micro-industry projects and facilitation of commercialization opportunities. As we elaborate on these impacts of the PIAL work, we also explore broader themes with respect to how the model has evolved over time, factors for success, and vision toward the future. We discuss the ways in which PIAL's gender work is contributing to a revival and revaluing of campesina culture, how it is challenging deeply entrenched norms of both femininities and masculinities, how it is engaging youth and fostering inter-generational knowledge-sharing, the ways in which it leverages the expertise and resources of formal research institutes to support locally-focused participatory initiatives and, finally, how it is building networks and partnerships that embed its work in institutional (e.g., government) settings at a variety of scales, thus helping to ensure use of local government funds for the work, and guaranteeing longevity independent of external funding.